2016
DOI: 10.1292/jvms.16-0302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D-allulose on glucose metabolism after the administration of sugar or food in healthy dogs

Abstract: D-allulose is a C-3 epimer of D-fructose and has recently been investigated for its hypoglycemic effects. In the present study, the effects of D-allulose on glucose metabolism were evaluated in healthy dogs administrated sugar or food. The oral administrations of D-allulose decreased plasma glucose concentrations after oral glucose or maltose administration, with a diminished plasma insulin rise. The glucose suppressive effect of D-allulose was also observed after intravenous glucose administrations without in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the present study, D-allulose administration did not affect the results of the glucose tolerance test. In contrast, a previous study has reported that a single administration of D-allulose (0.2 g/kg), 60 min before the intravenous glucose injection significantly lowers plasma glucose and insulin concentrations in dogs [ 19 ]. In the present study, the postadministration experiment was conducted one day after termination of D-allulose administration to evaluate the long-term cumulative effect of D-allulose on glucose metabolism.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…In the present study, D-allulose administration did not affect the results of the glucose tolerance test. In contrast, a previous study has reported that a single administration of D-allulose (0.2 g/kg), 60 min before the intravenous glucose injection significantly lowers plasma glucose and insulin concentrations in dogs [ 19 ]. In the present study, the postadministration experiment was conducted one day after termination of D-allulose administration to evaluate the long-term cumulative effect of D-allulose on glucose metabolism.…”
mentioning
confidence: 91%
“…The reported effects of D-allulose in rodents and humans may help the management of these pathologic conditions in dogs. In fact, D-allulose has been shown to suppress the rise in blood glucose following oral or intravenous glucose administration in dogs [ 19 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations